2013
DOI: 10.1037/a0032078
|View full text |Cite
|
Sign up to set email alerts
|

Behavior change techniques used to promote walking and cycling: A systematic review.

Abstract: Objective: Evidence on the effectiveness of walking and cycling interventions is mixed. This may be partly attributable to differences in intervention content, such as the cognitive and behavioral techniques (BCTs) used. Adopting a taxonomy of BCTs, this systematic review addressed two questions: (a) What are the behavior change techniques used in walking and cycling interventions targeted at adults? (b) What characterizes interventions that appear to be associated with changes in walking and cycling in adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(132 citation statements)
references
References 59 publications
5
127
0
Order By: Relevance
“…This finding may indicate that when participants focused more on the scheme's self-monitoring and feedback aspects, this was associated with less of a decline in PA and is in line with the results of the study's mediation analyses which found planning and habit formation are important mediators [5]. Previous research also shows that self-regulation techniques and self-monitoring are useful strategies for PA behaviour change [34,[59][60][61][62][63] and one previous systematic review of web-based interventions also highlights that web-based self-monitoring is a potentially effective technique [64]. Redeeming a higher proportion of earned points for rewards was associated with slightly higher PA levels at six months.…”
Section: Intervention Engagement and Physical Activitysupporting
confidence: 76%
“…This finding may indicate that when participants focused more on the scheme's self-monitoring and feedback aspects, this was associated with less of a decline in PA and is in line with the results of the study's mediation analyses which found planning and habit formation are important mediators [5]. Previous research also shows that self-regulation techniques and self-monitoring are useful strategies for PA behaviour change [34,[59][60][61][62][63] and one previous systematic review of web-based interventions also highlights that web-based self-monitoring is a potentially effective technique [64]. Redeeming a higher proportion of earned points for rewards was associated with slightly higher PA levels at six months.…”
Section: Intervention Engagement and Physical Activitysupporting
confidence: 76%
“…The theoretical basis of interventions were examined using the coding scheme developed by Taxonomy has been applied in systematic reviews to identify BCTs associated with effective approaches designed to influence a variety of behaviours including obesity management, physical activity, sexual health, alcohol use and cardiac rehabilitation (Martin et al, 2013;Burns et al, 2016;Heron et al, 2016;Prestwich et al, 2016;Bird et al, 2013) Findings were then compared and all disagreements were resolved through discussion between the two reviewers.…”
Section: Identification Of Behaviour Change Strategiesmentioning
confidence: 99%
“…Taxonomy has been applied in systematic reviews to identify BCTs associated with effective approaches designed to influence a variety of behaviours including obesity management, physical activity, sexual health, alcohol use and cardiac rehabilitation (Martin et al, 2013;Burns et al, 2016;Heron et al, 2016;Prestwich et al, 2016;Bird et al, 2013). To help understand behaviour change strategies the Behaviour Change Wheel (Michie et al, 2011) was used to identify the behaviour change function(s) in each intervention.…”
Section: Identification Of Behaviour Change Strategiesmentioning
confidence: 99%
“…Self-monitoring interventions have also been applied in the domain of physical activity. For example, a recent review on behaviour change techniques used to promote walking and cycling found that self-monitoring and intention formation were the most frequently coded behaviour change techniques for those two activities (Bird et al, 2013). There is also some evidence that they work -a study by Baker et al (2008) found that a pedometer-based self-monitoring walking program, incorporating a physical activity consultation, was effective in promoting walking and improving positive affect over 12 weeks in community based individuals.…”
Section: Introductionmentioning
confidence: 97%